Биологические особенности организма животных рода Sus - Хохлов, А.М.; Барановский, Д.И.; Смирнова, А.С. (Фактори експериментальної еволюції організмів, 2015)
Aims. During many years history of domestication of swine the profounds morphological, physiological and genetical changes have been occurred. Aim of ours investigations was estimation of morphological and biochemical peculiarity of sperm in Sus scrofa ferus and boars of modern breeds. Methods. The fresh sperm of Sus scrofa ferus have been investigated. By traditional methods the volume, concentration, activity, biochemical and other indexes of sperm wild and domestic boars have been determined. Used interferention microscope the frequents of various defects in structures of sperm, size, dry matter of heads, quantity DNA and protein have been determined. In bone tissue studying of wild and domestic animals morphological methods and methods of bone resistance studying were used Results. In Sus scrofa ferus length of sperm heads was reliable smaller of sizes sexual cells of modern swine breeds boars. However, for width of sperm heads and length of middle parts take place reliable advantage in boars Sus scrofa ferus. Middle part of sperms has mitochondrial apparate that promoting higer activity and better adaptation of wild Sus scrofa ferus sperm. Also, at experimental animals studying development of bone and muscle tissue, quality of production. Quality of production standing by content of mioglobin and elastin in animal muscle tissue. Conclusions. At fi rst time the native sperm from wild Sus scrofa ferus have been received and comparative analysis morphofunctional indexes of sperm wild boars and boars of modern breeds have been made. Method of interferention microscoping permissible reliable to estimate the morphological and genetical indexes of sperm wild and domestic boars. Biological set control in animal selection may be developed in all periods of ontogenesis or farming animal using. Keywords: DNA, mioglobin, bone, muscle.